PENGARUH TEKANAN WAKTU AUDIT DAN LOCUS OF CONTROL TERHADAP TINDAKAN YANG MENURUNKAN KUALITAS AUDIT - Kurnia Kurnia (EKUITAS (Jurnal Ekonomi dan Keuangan), 2011)
The objective of this study is to investigate the effect of audit time pressure and locus of control on reduced audit quality. Based on the literature review, it was hypothesized that audit time pressure and locus of control have a significant effect on reduced audit quality. This research was done on auditors of audit firms listing Bapepam-Lembaga Keuangan (LK). Data was collected through questionnaires. The respondents of this research are junior auditors, senior, supervisor, and manager. Data were analyzed using path analysis for testing hypothesis. The results show that audit time pressure and locus of control have a significant effect on reduced audit quality. Spesifically, this study indicate that auditors who experience greater level of time pressure are more likely to commit reduced audit quality. Under conditions of excessive time pressure, auditors failed to adequately use all relevant decision cues. The results also indicate that auditors who are more likely to engage in reduced audit quality tend to possess an external locus of control. This indicate that the personality characteristics (instance, locus of control) play a role increasing audit quality. Since an external locus of control is associated with higher acceptance of audit quality reduction behaviors, audit firms may need to tailor their professional development programs and management practices to reflect an auditor’s locus of control.